2017
DOI: 10.1093/eurheartj/ehx362
|View full text |Cite
|
Sign up to set email alerts
|

Infections, atherosclerosis, and coronary heart disease

Abstract: Atherosclerosis is a chronic inflammatory disease. Pathophysiological similarities between chronic infections and atherosclerosis triggered interest in a clinical association between these conditions. Various infectious microbes have been linked to atherosclerotic vascular disease in epidemiological studies. However, this association failed to satisfy the Koch's postulates of causation with multiple clinical trials demonstrating inefficacy of anti-infective therapies in mitigating atherosclerotic cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 71 publications
2
141
1
3
Order By: Relevance
“…Clinical reports have revealed a possible association of viral infections with atherosclerosis in humans, which was subsequently confirmed in mice (16). It has been proposed that infection modulates atherosclerosis progression by inducing substantial pathologic changes, such as oxidative stress and ER stress, in local endothelial cells, in smooth muscle cells and in immune (mainly T) cells (17,18). In addition, genetic variants of TLR4, the major receptor of LPS, were clinically associated with cardiovascular diseases, further supporting the role of inflammation in atherosclerosis (19).…”
mentioning
confidence: 95%
“…Clinical reports have revealed a possible association of viral infections with atherosclerosis in humans, which was subsequently confirmed in mice (16). It has been proposed that infection modulates atherosclerosis progression by inducing substantial pathologic changes, such as oxidative stress and ER stress, in local endothelial cells, in smooth muscle cells and in immune (mainly T) cells (17,18). In addition, genetic variants of TLR4, the major receptor of LPS, were clinically associated with cardiovascular diseases, further supporting the role of inflammation in atherosclerosis (19).…”
mentioning
confidence: 95%
“…Infections, as a stimulus of inflammation, have long been linked to the genesis, progression and instability of atherosclerotic plaques [24]. Multiple infectious agents, including influenza, have been shown to induce local pro-atherosclerotic mechanisms, such as expression of adhesion molecules, production of monocyte chemoattractant protein-1, oxidation of LDL, that lead to activation of endothelium, migration of leucocytes and eventually formation of lipid core [24-27].…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…Multiple infectious agents, including influenza, have been shown to induce local pro-atherosclerotic mechanisms, such as expression of adhesion molecules, production of monocyte chemoattractant protein-1, oxidation of LDL, that lead to activation of endothelium, migration of leucocytes and eventually formation of lipid core [24-27]. Infections have also been associated with increased smooth muscle cell proliferation in the vessel wall that contributes to plaque progression [24]. In an animal model of atherosclerosis, it has been shown that influenza infection promotes inflammation, smooth muscle cell proliferation, and fibrin deposition in atherosclerotic plaques, similar to unstable plaques after MI [28].…”
Section: Coronary Heart Diseasementioning
confidence: 99%
See 2 more Smart Citations